The effect of weight training to develop of some physical abilities and the achievement of the 50-meter freestyle swimmers - Mohammed Farhan, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The science of sports training has laid a basic foundation for all sports events and activities, and the link and overlap of the science of sports training with other sciences can be used to achieve the desired achievement. The effectiveness of training with weights in swimming is important because it increases the speed of the swimmer through the use of correct scientific methods, which will enable the coach to discover the extent achieved from training with weights that reach the shortest way and best performance and work to achieve the desired goals in the curricula and training units. The importance of the research is to identify the effect of weight training on the development of some physical abilities and achievement of the 50-meter freestyle swimmer because of its impact on the speed of the swimmer in cutting the distance and achieving the best time during the race and competition. After presenting, analyzing, and discussing the results, the most important conclusions were that exercises with weights have a positive effect in developing some selected physical abilities and achievement for the 50-meter freestyle swimmer. The most important recommendations were the need to pay attention to weight training for its impact on the development of research variables for the members of the research sample and the achievement of 50 free meters.